(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Suicidal hanging remains a significant health concern worldwide, including Bangladesh. Forensic medicine plays a pivotal role in investigating these tragic events, providing valuable insights into the circumstances surrounding the deaths. By meticulously examining ligature marks, the scene of the incident and post-mortem findings, forensic investigators can piece together the puzzle of a person’s final moments. Understanding the common patterns associated with suicidal hangings offers valuable information regarding the suicide incidences and a deeper understanding of the factors that contribute to such tragic acts. Objective: To find out the post-mortem findings of hanging among the victims who underwent autopsy examination. Methods: This cros-sectional descriptive study was conducted at the Department of Forensic Medicine, Shaheed Suhrawardy Medical College Hospital, Dhaka from January 2024 to June 2024. A total of 110 autopsies were performed on individuals who died due to suicidal hanging. Data were collected from inquest report, chalan and death certificate (in case of death in hospital) which included information on victim demographics, scene of the incident and suspected cause of death. Additional information was gathered from family members. During autopsies, forensic investigators examined the body for ligature mark, ligature material, knot type, neck injuries, cyanosis, congestion etc. A standardized protocol was followed to ensure data accuracy and consistency. Results: The majority of victims were female (59.1%) and aged 21-30 years (55.5%). Most of them were married (64.5%) and resided in urban areas (77.3%). The most common ligature material was rope (65.5%), followed by scarves (34.5%). The primary suspected cause of hanging was quarrels between couples (35.5%), followed by financial problems, psychiatric illness and drug addiction etc. The majority of incidents occurred at night (52.7%). Post-mortem findings included ligature marks above the thyroid cartilage, fractures in the thyroid cartilage and hyoid bone, cyanosis, glistening beneath ligature marks, congestion, petechial hemorrhage etc. Conclusion: The findings highlight the urgent need for targeted suicide prevention strategies, including improved access to mental health services, education and awareness campaigns, and support systems for individuals at risk. Future research should explore the long-term impact of suicidal hanging on families and communities, as well as the effectiveness of different preventive interventions. JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 33-36